The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1002/bit.22561
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization in the CDR2 of a monoclonal antibody: Binding analysis and factors that influence the isomerization rate

Abstract: Isomerization of a monoclonal antibody is one of the common routes of protein degradation. An isomerization in the complementarity-determining region (CDR) was found previously and is investigated in depth in this work. Affinity analysis proves that the antibody with one isomerized heavy chain has lower binding. Binding constants were determined, and exhibited a slower on-rate in conjunction with a faster off-rate for this isomerization. To determine the role of the buffer on the rate of isomerization, this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The deamidation hotspot at HC‐Asn328 under the acidic condition (pH 5.1 in this work) was not reported by Harris et al, which may be because of that trastuzumab was not stressed and tested in the acidic pH in their work. It is known that normally the deamidation of Asn residue proceeds favorably at neutral and basic pH values and the isomerization of Asp residue proceeds faster at acidic pH values (e.g., pH <6.0) . A special case of deamidation in acidic solution was recently reported for this Asn328 in VSNK peptide, in which deamidation was not detected in neutral pH .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The deamidation hotspot at HC‐Asn328 under the acidic condition (pH 5.1 in this work) was not reported by Harris et al, which may be because of that trastuzumab was not stressed and tested in the acidic pH in their work. It is known that normally the deamidation of Asn residue proceeds favorably at neutral and basic pH values and the isomerization of Asp residue proceeds faster at acidic pH values (e.g., pH <6.0) . A special case of deamidation in acidic solution was recently reported for this Asn328 in VSNK peptide, in which deamidation was not detected in neutral pH .…”
Section: Discussionmentioning
confidence: 93%
“…Like other proteins, therapeutic mAbs are susceptible to a variety of chemical and physical degradation reactions during manufacturing, formulation storage and in vivo usage . Asparagines (Asn) deamidation and aspartate (Asp) isomerization are the most common pathways for the chemical degradation of mAbs, which could affect the in vitro stability, in vivo biological functions, and bioavailability of a therapeutic mAb . It has been reported that several IgG1 mAbs lost their bioactivities because of the deamidation and/or isomerization in their complementary determining regions (CDRs) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such reaction makes Asp being considered as a protein hotspot of isomerization. Asp isomerization has been reported on antibodies by multiple papers [4244]. Comparing to Asn deamidation, Asp isomerization has a higher rate at low pH (< 5.5) [1].…”
Section: Resultsmentioning
confidence: 99%
“…These heterogeneities include aggregation, fragmentation, deamidation, oxidation, N-and C-terminal differentiations. [2][3][4][5][6][7][8][9][10][11] Several analytical methods have been developed for these purposes, for example, SDS polyacrylamide gel electrophoresis for the determination of the purity of proteins, size exclusion chromatography for aggregation, ion exchange chromatography or hydrophobic interaction chromatography for the detection of deamidation and oxidation variants, and Ellman's assay for quantification of free thiol groups. 12,13 Capillary-based SDS electrophoresis (CE-SDS) is one version of the capillary gel electrophoresis (CGE) using soluble linear polymers.…”
Section: Introductionmentioning
confidence: 99%